2017
DOI: 10.3847/1538-4357/aa74da
|View full text |Cite
|
Sign up to set email alerts
|

Lensing of Fast Radio Bursts by Plasma Structures in Host Galaxies

Abstract: Plasma lenses in the host galaxies of fast radio bursts (FRBs) can strongly modulate FRB amplitudes for a wide range of distances, including the ∼ Gpc distance of the repeater FRB121102. To produce caustics, the lens' dispersion-measure depth (DM ), scale size (a), and distance from the source (d sl ) must satisfy DM d sl /a 2 0.65 pc 2 AU −2 cm −3 . Caustics produce strong magnifications ( 10 2 ) on short time scales (∼ hours to days and perhaps shorter) along with narrow, epoch dependent spectral peaks (0.1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
261
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 186 publications
(265 citation statements)
references
References 32 publications
4
261
0
Order By: Relevance
“…Here we will discuss the mechanism and explore the implications of the possible connection with our observations. Plasma lenses have been considered previously in the form of a Gaussian cloud (Clegg et al 1998;Cordes et al 2017) or folded current sheets (Simard & Pen 2018) and are consistent with observed "extreme scattering" events (Fiedler et al 1987;Coles et al 2015;Bannister et al 2016;Kerr et al 2018). These over-or under-densities of interstellar free electrons can alter the TOAs in a frequency-dependent manner and modulate pulse fluxes.…”
Section: Plasma Lensingmentioning
confidence: 94%
See 4 more Smart Citations
“…Here we will discuss the mechanism and explore the implications of the possible connection with our observations. Plasma lenses have been considered previously in the form of a Gaussian cloud (Clegg et al 1998;Cordes et al 2017) or folded current sheets (Simard & Pen 2018) and are consistent with observed "extreme scattering" events (Fiedler et al 1987;Coles et al 2015;Bannister et al 2016;Kerr et al 2018). These over-or under-densities of interstellar free electrons can alter the TOAs in a frequency-dependent manner and modulate pulse fluxes.…”
Section: Plasma Lensingmentioning
confidence: 94%
“…For a stationary lens situated halfway between the Earth and pulsar, with the pulsar and Earth velocities aligned, v eff ≈18 km s −1 given the proper motion, implying L18 km s −1 ×7.6 years≈30 au. Refraction from such a lens may explain the possible non-ν −2 delays (Equation (5) or see Foster & Cordes 1990) from our multicomponent fitting but again we do not see significant changes in the scattering parameters from the small ΔBIC value though we have only tested a small number of possible models and lensing can produce non-ν −2 delays that have complex dependencies in frequency and time (Cordes et al 2017); assuming that Model B is correct, then the fluctuations in Figure 3 do show significant temporal variations. If refraction does explain the observed delays, then our crude analysis suggests that the change in n e with respect to the surrounding medium is large and/or the lens is highly compact for the geometric delay to become important as per Equation (5); however, the barycentric delay becomes important for compact lenses as suggested above in Equation (6).…”
Section: Plasma Lensingmentioning
confidence: 98%
See 3 more Smart Citations